UPLOAD SOCIAL RESOURCES IN THE SOCIALIZATION OF DIGITAL LITERATURE IN THE DEVELOPMENT COMMUNITIES OF KAMPOENG DJOEANG - M. Muttaqien; Irfa Puspitasari; Fadhila Inas Pratiwi (Jurnal Layanan Masyarakat (Journal of Public Services), 2022)
Ease of access to information is a definite consequence of the deepening of globalization. Mode of interaction and communication advancement are characteristic that can now be easily recognized through technological developments. This raise a problem related to less optimum usage of the internet amid the high use of digital applications. The existing conditions lead to a lack of people's ability to both understand digital objects and the benefits that is contained. The implementation of community service in partnership with Kampoeng Djoeang aims to introduce and upload social resources related to digital literacy skills which are now crucial in the midst of the Covid-19 Pandemic. The method used is a series of training in three stages, namely (1) analysis of community needs, (2) socialization of digital literacy, and (3) evaluation and feedback. It was found that practical forms of training were the answer to two people's needs, namely (1) digital literacy education by providing information analysis skills and (2) understanding legal and ethical references in social media.